Integration of Lubuklinggau Local Wisdom in the Development of Mathematics Teaching Modules for PGSD UNPARI Students: Kearifan Lokal, Modul Ajar Matematika, Lubuklinggau, PGSD, - Maria Luthfiana; Nur Fitriyana (Postgraduate, University of Mataram, 2025)
Local wisdom represents a valuable source of cultural knowledge that can be integrated into mathematics education to promote meaningful and contextual learning. In the Lubuklinggau region, however, such integration has not been optimally realized, particularly in the development of higher education teaching materials. This research seeks to design and validate a mathematics teaching module incorporating Lubuklinggau’s local wisdom for PGSD students at UNPARI. Employing a research and development (R&D) approach with the ADDIE framework—comprising analysis, design, development, implementation, and evaluation—data were gathered through interviews, literature review, expert assessment, and limited classroom trials. Descriptive and qualitative analyses were applied to evaluate the results. Validation outcomes demonstrated high levels of validity with average scores of 0.85 (content), 0.87 (media), and 0.89 (language). Lecturers and students also provided very positive responses, with practicality scores of 4.6 and 4.43, respectively. The findings indicate that the developed module is both feasible and effective in improving students’ contextual understanding of mathematics while fostering the appreciation and preservation of local cultural values within the university setting.